Boletim do Clube Filatélico de Portugal - dir. Marcos Pereira (João Tavares)
Existências: Nº179 (jun. 1966); Nº181 (ago. 1966); Nº193 (ago. 1967); Nº194 (set. 1967); Nº198 (jan. 1968) - nº201 (abr. 1968); Nº215 (jun. 1969); Nº222 (jan. 1970).